Assessing the Role of Selected Osmolytes in Mediterranean High-Mountain Specialists - Magaña Ugarte, Rosina; Escudero, Adrián; Gavilán, Rosario G. (Frontiers in Ecology and Evolution, 2021)
Despite the constraining weight of summer drought over plant life which distinguishes Mediterranean high-mountains, and its anticipated exacerbation under the current climate crisis, there is still little knowledge of the underlying drought-endurance mechanisms in Mediterranean high-mountain species, such as osmolyte accumulation. To fill this gap, we studied the role of two of the most frequent osmoregulators in plants, proline and osmotically active carbohydrates (OAC), as pointers of the drought-stress response in seven high-mountain plant species representative of the high-mountain plant communities in Central Spain, along an elevation gradient. Overall, our results are consistent with the escalation of summer drought and suggest the involvement of osmolytes to sustain plant activity in these specialists during the growing season. Proline content showed a steadily increasing pattern in line with the seasonal aggravation of summer drought. The significant rise in mean proline in most species, coinciding with the periods with the greatest decline in soil water content, suggests the recurrent role of proline in the drought-stress response in the studied specialists. The lack of significant differences between elevations and the minimal seasonal variations in the OAC content suggest a fixed OAC content independent of functional type, to sustain metabolic functions under summer drought. Moreover, these findings allow inferring the action of both OAC and proline as osmoregulators, allowing to sustain plant functions in these specialists under atypically dry conditions. Overall, our findings are consistent with proline as a major osmoprotectant strategy over OAC buildup in these specialists, which may be related to an adaptation strategy associated with the briefness of the growing season and the incidence of less favorable conditions in Mediterranean high-mountains.